Structural and Theoretical Evidence of the Depleted Proton Affinity of the N3-Atom in Acyclovir - Esther Vílchez-Rodríguez; Inmaculada Pérez-Toro; Antonio Bauzá; Antonio Matilla-Hernández (Crystals, 2016)
The hydronium salt (H3O)2[Cu(N7–acv)2(H2O)2(SO4)2]·2H2O (1, acv = acyclovir) has been synthesized and characterized by single-crystal X-ray diffraction and spectral methods. Solvated Cu(OH)2 is a by-product of the synthesis. In the all-trans centrosymmetric complex anion, (a) the Cu(II) atom exhibits an elongated octahedral coordination; (b) the metal-binding pattern of acyclovir (acv) consists of a Cu–N7(acv) bond plus an (aqua)O–H···O6(acv) interligand interaction; and (c) trans-apical/distal sites are occupied by monodentate O-sulfate donor anions. Neutral acyclovir and aqua-proximal ligands occupy the basal positions, stabilizing the metal binding pattern of acv. Each hydronium(1+) ion builds three H-bonds with O–sulfate, O6(acv), and O–alcohol(acv) from three neighboring complex anions. No O atoms of solvent water molecules are involved as acceptors. Theoretical calculations of molecular electrostatic potential surfaces and atomic charges also support that the O-alcohol of the N9(acv) side chain is a better H-acceptor than the N3 or the O-ether atoms of acv.